Duplex Ultrasonography Has Limited Utility in Detection of Postoperative DVT after Primary Total Joint Arthroplasty. Issue 2 (July 2016) - Vira, Shaleen; Ramme, Austin J.; Alaia, Michael J.; Steiger, David; Vigdorchik, Jonathan M.; Jaffe, Frederick
Background: Duplex ultrasound is routinely used to evaluate suspected deep venous thrombosis after total joint arthroplasty. When there is a clinical suspicion for a pulmonary embolism, a chest angiogram (chest CTA) is concomitantly obtained. Questions/Purposes: Two questions were addressed: First, for the population of patients who receive duplex ultrasound after total joint arthroplasty, what is the rate of positive results? Second, for these patients, how many of these also undergo chest CTA for clinical suspicion of pulmonary embolus and how many of these tests are positive? Furthermore, what is the correlation between duplex ultrasound results and chest CTA results? Methods: A retrospective chart review was conducted of total joint replacement patients in 2011 at a single institution. Inclusion criteria were adult patients who underwent a postoperative duplex ultrasonography for clinical suspicion of deep venous thrombosis (DVT). Demographic data, result of duplex scan, clinical indications for obtaining the duplex scan, and DVT prophylaxis used were recorded. Additionally, if a chest CTA was obtained for clinical suspicion for pulmonary embolus, results and clinical indication for obtaining the test were recorded. The rate of positive results for duplex ultrasonography and chest CTA was computed and correlated based on clinical indications. Results: Two hundred ninety-five patients underwent duplex ultrasonography of which only 0.7% were positive for a DVT. One hundred three patients underwent a chest CTA for clinical suspicion of a pulmonary embolism (PE) of which 26 revealed a pulmonary embolus, none of which had a positive duplex ultrasound. Conclusion: Postoperative duplex scans have a low rate of positive results. A substantial number of patients with negative duplex results subsequently underwent chest CTA for clinical suspicion for which a pulmonary embolus was found, presumably resulting from a DVT despite negative duplex ultrasound result. A negative duplex ultrasonography should not rule out the presence of a DVT which can embolize to the lungs and thus should not preclude further workup when clinical suspicion exists for a pulmonary embolus.